Jack Hills (Yilgarn, Western Australia) - Wilde, Simon (Springer-Verlag, 2011)
Jack Hills is the name of a low range of hills located in the Murchison District of Western Australia, approximately 800 km north of Perth. Since 1986, the area has been internationally known as the site of the world’s oldest minerals. These are detrital zircon grains up to 4,404 Ma old.